Definition and Role of Translation In Enriching Cultural Identity - CHENNI, Fairouz (Journal of Human Sciences, 2020)
Through time and different civilizations, translation has been one of the most important concerns of man. This is in fact what enables the members of human societies to communicate and is the basis of all development. This article includes a definition of translation and its importance in the unification of the language and its role in the establishment of the communicative function. It has always been an important factor in the rebirth of the nation because it allows it to remain homogeneous, through it that literatures come closer. There is also a historical overview of the translation between the Arab world and the West and the passage of literary texts from one language to another, in this case Arabic texts confirming Arab cultural identity. The translation of the literary effect whether related to poetry or prose, is among the most difficult translations for what it implies as aesthetic traits and specificities. The translation operation allows us to access another universe.